Indoor and Outdoor Air Pollution Monitoring Developments in the Municipality of Thessaloniki – Preliminary Actions from Three European Funded Projects - Papastergios, Georgios; Tzoumaka, Paraskevi; Kelessis, Apostolos (Bulletin of the Geological Society of Greece, 2019)
Air pollution has been one of the first environmental problems to be addressed by the EU and for this reason clean air is considered essential to good health. Information availability and understanding of the air quality issue is essential part of tackling it with efficiency. Having the latter in mind, the Municipality of Thessaloniki has considered relative environmental actions as an important priority and made significant efforts to include them in its short-term and long-term, already developed, strategies. Through these strategies the Municipality became partner in three important EU funded projects that are dealing with indoor and outdoor air pollution monitoring actions, namely CUTLER, AIRTHINGS, and LIFE SMART IN'AIR. The successful implementation of these projects will add to the knowledge of indoor and outdoor air quality in the City of Thessaloniki, whereas, at the same time, will improve the resilience of the city and the well being of its citizens.